Enhancing Guided Writing Skills: The Impact of Mufradat and Qawaid Mastery in Arabic Language Learning - Herdah Herdah; Raodhatul Jannah; Nurul Atika; Mirdawati Mirdawati (STAI Hubbulwathan Duri, 2025)
Mastery of mufradat (vocabulary) and qawaid (grammar) is crucial in Arabic language acquisition at all educational levels, including at Madrasah Aliah YMPI Rappang. Proficiency in these areas is strongly linked to students’ ability to produce insya' muwajjah (guided writing). This study employed an ex post facto design to examine the relationship between mufradat and qawaid mastery and Arabic writing skills. The population consisted of 113 eleventh-grade students, from which a sample of 53 was selected through proportionate stratified random sampling using the Slovin formula. Data collection involved standardized tests measuring vocabulary, grammar, and guided writing proficiency. Analysis was conducted using product-moment correlation and multiple linear regression techniques. Findings revealed that mufradat mastery (X₁) had a significant positive effect on writing skills (Y), with a correlation coefficient of 0.140. Qawaid mastery (X₂) showed a stronger impact, with a coefficient of 0.536. Combined, both variables significantly influenced writing ability, as evidenced by an F-value of 22.879. These results underscore the importance of integrating vocabulary and grammar mastery into the Arabic curriculum to enhance students’ writing competence. Targeted instructional strategies focusing on both elements can substantially support students’ language development.